2013
DOI: 10.2478/s11534-013-0180-x
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon double ionization of helium: investigating the importance of correlation in the final state

Abstract: Abstract:In this paper, we present theoretical results for the process of non-sequential two-photon double ionization of helium at the photon energy 42 eV. Our approach is based on solving the time-dependent Schrödinger equation in a B-spline based numerical framework. Information about the process is obtained by extracting the double-ionized component by means of uncorrelated final states. The total (generalized) cross section for the process is extracted, as well as differential cross sections resolved in el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…II, the process of extracting the double-continuum component is associated with an error which is controlled by the postpropagation technique. As found in similar studies [16,24], the error is relatively small (of the order of a few percent) and diminishes rapidly only with a few cycles of postpropagation.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…II, the process of extracting the double-continuum component is associated with an error which is controlled by the postpropagation technique. As found in similar studies [16,24], the error is relatively small (of the order of a few percent) and diminishes rapidly only with a few cycles of postpropagation.…”
Section: Resultssupporting
confidence: 69%
“…The computational details of our scheme are described in [19], and it has been applied successfully to the study of various laser-induced processes in two-electron systems [19,20,24,36,[45][46][47]. A short summary of the numerical details will be reiterated here for the convenience of the reader.…”
Section: Theory and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…This causes the mean distance between the ionized electrons to increase rapidly, thus reducing the importance of the electron-electron interaction. It is usually found that the error associated with such an approach becomes small after only a few cycles of postpropagation [9,17].…”
Section: B the Full Solutionmentioning
confidence: 99%